Growth and Survival Rate of Red Tilapia (Oreochromis sp) with the Frequency of Addition of Molasses to Biofloc Systems - Manalu, Edison Roganda; Mulyadi, Mulyadi; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted from October to December 2018 in the Technical Services Unit (UPT) Pool and Hatchery, Faculty of Fisheries and Marine Affairs, Riau University, Pekanbaru. The purpose of this study was to determine the frequency of addition of molasses in the biofloc system to the growth and survival of red tilapia (Oreochromis sp). The method used in this study is the experimental method using a Completely Randomized Design (CRD) of 1 factor with 4 levels of treatment and 3 replications. P0: Treatment without giving molasses (control), P1: Frequency of giving molasses 150 ml / m3 and given every 5 days, P2: Frequency of giving molasses 150 ml / m3 and given every 10 days, P3: Frequency of giving molasses 150 ml / m3 and given every 15 days. The frequency of adding molasses of 150 ml / m3. The results showed that the best treatment was treatment P2: The frequency of giving molasses 150 ml / m3 and given every 10 days. Weight growth an average of 4.96 grams, absolute weight growth of 3.82 grams, the absolute length of 5.29 cm, specific rate growth of 3.68%, feed efficiency of 106.34%, feed conversion ratio (FCR) of 0.83, livelihoods ( SR) 85%, floc volume 21 ml / l. Thewater qualityparameters aretemperature 26-280C, dissolved oxygen is 3.54-4.40 mg / l, pH 6-7, and ammonia 0.0032 - 0.0090 mg / l. Keywords: Molasses, Biofloc, Red Tilapia (Oreochromis sp)